Evaluation of Sensitivity to Slaking by Bulk Density Measurements of Disrupted Fragments (Aggregates) - Mokhtaruddin, A.M; Boodt, M (1983)
The study shows that other than the four factors viz: slaking, dispersion, carbonate or gypsum content and flocculation, the size and bulk density of disrupted aggregates are also important when classifying the soils into their corresponding water coherence classes. It was found that for the Ultisols and the Oxisols, the aggregates will not slake further if they have a size of> 1 mm and a bulk density ofat least 1.7 g cm-3